ANALISIS FAKTOR – FAKTOR YANG MEMPENGARUHI KEMISKINAN DI KABUPATEN TABANAN - I Dewa Gede Aristana; Agus Putra Mardika; Prayana, I Kadek Wira Dharma (Universitas Tabanan, 2023)
Poverty is a highly complex social issue influenced by various interconnected factors, including Minimum Wage, Gross Regional Domestic Product, and Population Size. The hypotheses are as follows: (1) Minimum Wage has a negative and significant partial effect on poverty in Tabanan Regency, (2) Gross Regional Domestic Product has a negative and significant partial effect on poverty in Tabanan Regency, (3) Population Size has a positive and significant partial effect on poverty in Tabanan Regency, (4) Minimum Wage, Gross Regional Domestic Product, and Population Size have a significant partial and simultaneous effect on poverty in Tabanan Regency. Minimum Wage (X1) has a negative and significant impact on Poverty (Y) in Tabanan Regency. The lower the minimum wage received by the community, the higher the poverty rate. Gross Regional Domestic Product (X2) has a negative and significant impact on Poverty (Y) in Tabanan Regency. The lower the GRDP received by the community, the higher the poverty rate. Population Size (X3) has a positive and significant impact on Poverty (Y) in Tabanan Regency. The higher the population size in Tabanan Regency, the higher the poverty rate. Minimum Wage, Gross Regional Domestic Product, and Population Size have a simultaneous impact on Poverty.